IMPLEMENTASI SERVICE EXCELLENCE OLEH CUSTOMER SERVICE TERHADAP PENINGKATAN DANA TABUNGAN PT BANK DKI KANTOR CABANG JAKARTA BARAT - Annisa Adriana Putri (2021)
In the banking industry, savings are one of the third party funds that can affect the success rate of a bank. The success rate of a bank is seen from the amount of deposit funds at PT Bank DKI West Jakarta Branch Office. If the source of funds increases, it is because the number of potential customers of a bank product increases and also because of service excellence in its implementation. Service excellence or what is called excellent service has a very important influence in determining the condition of the bank. In addition, PT Bank DKI West Jakarta Branch also has various types of savings for its customers, such as Simpeda, Monas and TabunganKu where these savings products have different types. The increase in savings funds at PT Bank DKI West Jakarta Branch Office can be caused by various things, one of which is the economic factor of the people starting to improve. The implementation of service excellence by customer service to help increase savings funds of PT Bank DKI West Jakarta Branch Office must have special skills possessed by a customer service such as having the skills of caring attitude towards customers, being able to see differences in customer characteristics, and providing excellent service. good, both in terms of appearance, behavior, as well as facilities and infrastructure at the bank.